Turning Strategy Into Results - Sull, Donald; Turconi, Stefano; Sull, Charles; Yoder, James (MIT Sloan Management Review, 2018)
Businesses develop strategies to address complex, multi-layered business environments and challenges - but to execute a strategy in a meaningful way, it must produce a set of specific priorities focused on achieving clear goals. Rather than trying to boil the strategy down to a pithy statement, executives will get better results if they develop a small set of actions that everyone gets behind.